Race, Nationalism and the State in British and American Modernism - Chu, Patricia E (Cambridge University Press, 2013)
The human monster. An ancient notion whose frame of reference is law . . . the monster’s field of appearance is a juridico-biological domain . . . what makes a human monster a monster is not just its exceptionality relative to the species form; it is the disturbance it brings to juridical regularities (whether it is a question of marriage laws, canons of baptism, or rules of inheritance).